2022
DOI: 10.3390/ijerph191912547
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Residual Health Risk of Organochlorine Pesticides in Fresh Vegetables in the Suburb of Changchun, Northeast China

Abstract: In this study, eleven organochlorine pesticides (OCPs) in fresh vegetables in the Changchun suburb were investigated, and their potential health risks were evaluated. The average concentrations of OCPs in edible parts of vegetables were found in the following descending order: Σhexachlorocyclohexanes (ΣHCHs) (6.60 µg·kg−1) > Σdichlorodiphenyltrichloroethanes (ΣDDTs) (5.82 µg·kg−1) > ΣChlordanes (2.37 µg·kg−1) > heptachlor (0.29 µg·kg−1). Moreover, OCPs in different types of vegetables exceeded the max… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“… MATRIX No. OF COMPOUNDs LOD LOQ RECOVERY RSD INSTRUMENT/INSTRUMENTAL CONDITIONS/TOTAL RUN TIME REFERENCE Vegetables 11 0.07–0.18 76.21–93.51 4.76–11.1 GC-ECD: “Splitless, the initial temperature at 100 °C for 1 min, ramping to 190 °C at 12 °C/min, and held for 8 min, followed by continuous ramping to 250 °C at 3 °C/min, and held for 10 min” [ 290 ] Vegetable 10 0.0011 to 0.021 0.0013–0.034 95–110 HPLC: “40 % A at 70.1–75.0 min and 7 % A at 75.1–90.1 min. The column temperature was maintained at 30 °C” [ 291 ] Vegetables 20 0.01–0.08 0.03–0.24 88.6–102 <6 GC-MSD: “Splitless, Initial oven temperature was 150 °C, increase to 280 °C at 6 °C/min and final temperature was 300 °C” [ 292 ] Leafy vegetable(spinach, lettuce, oilseed rape, cabbage 8 0.15–0.32 0.45–0.96 78.6–107.7 1.1–7.5 GC-MS: “Splitless, the oven temperature program was set as follows: 50 °C as initial temperature, maintained for 1 min, raised to 200 °C at 20 °C/min, raised to 230 °C at 5 °C/min, and maintained for 5 min, raised to 280 °C at 10 °C/min, and held for 1 min.…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
“… MATRIX No. OF COMPOUNDs LOD LOQ RECOVERY RSD INSTRUMENT/INSTRUMENTAL CONDITIONS/TOTAL RUN TIME REFERENCE Vegetables 11 0.07–0.18 76.21–93.51 4.76–11.1 GC-ECD: “Splitless, the initial temperature at 100 °C for 1 min, ramping to 190 °C at 12 °C/min, and held for 8 min, followed by continuous ramping to 250 °C at 3 °C/min, and held for 10 min” [ 290 ] Vegetable 10 0.0011 to 0.021 0.0013–0.034 95–110 HPLC: “40 % A at 70.1–75.0 min and 7 % A at 75.1–90.1 min. The column temperature was maintained at 30 °C” [ 291 ] Vegetables 20 0.01–0.08 0.03–0.24 88.6–102 <6 GC-MSD: “Splitless, Initial oven temperature was 150 °C, increase to 280 °C at 6 °C/min and final temperature was 300 °C” [ 292 ] Leafy vegetable(spinach, lettuce, oilseed rape, cabbage 8 0.15–0.32 0.45–0.96 78.6–107.7 1.1–7.5 GC-MS: “Splitless, the oven temperature program was set as follows: 50 °C as initial temperature, maintained for 1 min, raised to 200 °C at 20 °C/min, raised to 230 °C at 5 °C/min, and maintained for 5 min, raised to 280 °C at 10 °C/min, and held for 1 min.…”
Section: Results and Discussion: Literature Reviewmentioning
confidence: 99%
“…Among the compounds examined, levels of cypermethrin were the most abundant. Lastly, vegetables had a significantly higher aggregate concentration of residues than fruits, and this was expected, since vegetables (leafy ones in particular) are physiologically more prone to pesticide pollution than fruit crops [ 19 , 20 ]. The differences in residue concentrations can be partially explained by the differences in the persistence and dissipation rates of these residues, as well as weather conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In Dhaka, Bangladesh, pesticide residues and OCPs, in particular, have been detected in 45% of vegetables and 40% of fruits examined, much lower than the detection rate observed in the present study [ 21 ]. In Changchun, Northeast China, the pesticides detection rate was also lower at 47–71% [ 20 ]. A 2011 study in Accra metropolis, Ghana, revealed that 51% of the fruits and vegetables analyzed gave results of traces of pesticide residues.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found OCP residues in 11 types of vegetable oils: olive, corn, colza, camellia, peanut, soybean, linseed, blend, sunflower, and rice, with the highest concentration of OCPs found in sesame oil samples [ 25 ]. Multiple OCPs pesticide residues above the MRLs (HCHs; Drins; Heptachlor; Chlordane; DDT) were found in vegetable samples of tomato, cabbage, cucumber, carrot, eggplant, watermelon, and lettuce [ 26 , 27 , 28 ]. In China, OCP contaminations of Chinese cabbage and Welsh onion mainly originate from new inputs of lindane, while eggplant, pepper, cucumber, and radish accumulate historical residues of lindane in soil [ 28 ].…”
Section: Overview Of Pesticides In Foodmentioning
confidence: 99%
“…Multiple OCPs pesticide residues above the MRLs (HCHs; Drins; Heptachlor; Chlordane; DDT) were found in vegetable samples of tomato, cabbage, cucumber, carrot, eggplant, watermelon, and lettuce [ 26 , 27 , 28 ]. In China, OCP contaminations of Chinese cabbage and Welsh onion mainly originate from new inputs of lindane, while eggplant, pepper, cucumber, and radish accumulate historical residues of lindane in soil [ 28 ]. The milk samples containing residues of DDT, DDE, dieldrin, Ɣ-HCH, α-endosulfan, β-endosulfan, and endosulfan sulfate are derived from animals contaminated by feeding [ 29 , 30 ].…”
Section: Overview Of Pesticides In Foodmentioning
confidence: 99%